(untitled) (CIPEEX, 2025)
The SmartFinance project was developed within the Software Engineering course with the primary goal of providing a comprehensive technological solution for micro-entrepreneurs. The project aims to address the fundamental challenges faced by small business owners, particularly in the areas of financial and inventory management. Effective management of these aspects is crucial for ensuring long-term sustainability and business growth. The solution is designed to simplify processes, giving entrepreneurs the tools they need to track finances and manage stock efficiently. Problem Identification Micro-entrepreneurs frequently encounter difficulties in managing their business finances and inventory. The absence of proper tools for tracking financial transactions often leaves business owners with a limited understanding of their financial status. This lack of insight can lead to poor decision-making, which negatively affects the overall health of the business. Similarly, ineffective inventory management can cause significant financial losses. Overstocking results in unnecessary expenses, while understocking may lead to missed sales opportunities, harming profitability. These inefficiencies underline the importance of providing a reliable and user-friendly solution for small businesses. Justification The creation of SmartFinance is driven by the need to offer a technological solution that simplifies and optimizes business operations for micro-entrepreneurs. Efficient management of finances and inventory is key to maintaining business viability. By providing the right tools, SmartFinance enhances operational efficiency, enabling entrepreneurs to focus on business growth. Additionally, effective inventory control ensures businesses are well-stocked without incurring excess costs. The platform not only aids in day-to-day management but also delivers valuable insights for strategic decision-making. On a broader scale, supporting micro-entrepreneurs plays a critical role in fostering local economic development, as small businesses are vital contributors to regional economies. Objectives SmartFinance has several core objectives aimed at improving the financial and operational performance of micro-enterprises: • Simplify Financial Management: The platform provides an intuitive interface for users to log financial transactions such as sales, purchases, expenses, and revenues. This feature ensures micro-entrepreneurs have a clear and detailed view of their financial status, supporting more informed decisions. • Efficient Inventory Management: Entrepreneurs can effectively manage their inventory by tracking product inputs and outputs, monitoring stock levels, and setting up restocking alerts. These functions help prevent overstocking and stockouts, which can directly impact profitability. • Process Optimization: The tool helps micro-entrepreneurs identify areas of improvement in both financial and inventory management. By offering detailed insights and analysis, SmartFinance supports more efficient business processes. • Foster Business Growth: The platform empowers micro-entrepreneurs with the data and tools they need to manage their businesses effectively. By simplifying complex processes, SmartFinance allows business owners to focus on strategic planning and sustainable growth. Methodology The development of SmartFinance followed an agile, iterative process. This approach allowed for continuous improvements throughout the project, incorporating user feedback at different stages. The app version of SmartFinance was first prototyped using Figma, a tool that helped design user interfaces. The mobile app was developed with React Native, allowing it to function across multiple platforms, including both Android and iOS devices. For the web version, front-end technologies such as HTML5, CSS3, and React.js were used, while the back-end was built using Python and Flask to handle API integrations. This combination of technologies ensures that SmartFinance is both scalable and accessible to a wide range of users. Conclusion SmartFinance provides an essential solution to the financial and inventory management challenges faced by micro-entrepreneurs. By using modern technologies and a user-centered approach, the platform offers a practical and scalable tool that supports business growth and sustainability. Its simplicity and effectiveness make SmartFinance a valuable resource for small business owners seeking to improve their operational efficiency.